Shear behaviour of polypropylene fibrer-einforced-concrete beams without stirrups - Arslan, Guray; Keskin, Riza Secer Orkun; Ozturk, Mehdi (ICE PUBLISHING, 2017)
The structural performance of reinforced-concrete (RC) beams can be enhanced by introducing various types of randomly dispersed discrete fibres into the concrete matrix. While the shear behaviour of steel fibre RC beams has been studied substantially, research focusing on the shear behaviour of polypropylene fibre RC beams is limited. In the study reported here, the influence of polypropylene fibres on the shear behaviour of RC beams without stirrups was experimentally investigated. The test specimens comprised two RC beams and nine polypropylene fibre RC beams. The main test variables were the shear span-to-effective depth ratio and the volume fraction of polypropylene fibres. The beams were tested under a concentrated load at mid-span. It was found that both the shear strength and ductility of the beams were improved by adding polypropylene fibres, but the addition of polypropylene fibres even at 3% by volume was not able to change the failure mode for beams with shear span-to-effective depth ratios of 2.5 and 3.5. Based on an evaluation of the experimental results, a previously proposed equation for predicting the shear strength of steel fibre RC beams without stirrups was revised to predict the shear strength of polypropylene fibre RC beams without stirrups.
Keywords: beams & girders; composite structures; concrete structures; EFFECTIVE-DEPTH RATIO; STEEL-FIBER; SYNTHETIC-FIBERS; FIBROUS CONCRETE; STRENGTH; REINFORCEMENT; Construction & Building Technology; Engineering